Perancangan Sistem Informasi Desa Sibolangit Berbasis Website dengan Metode Waterfall - Ginting, Yoki Fernedi; Malau, Emerson Porman (UNIKA Santo Thomas, 2024)
The development of information technology has had a significant impact on various aspects of life, including the governance of rural areas. With the allocation of village funds from the central government, rural development has progressed rapidly. The utilization of information technology in village governance has become a crucial need to enhance service quality to the community. This research focuses on the development of a web-based village information system to improve service delivery in Desa Sibolangit. The system is designed to facilitate easy access to information, promote village economic potential, and provide accurate data on population and other vital aspects. The research adopts the Waterfall methodology, which allows systematic development through stages of needs analysis, system design, implementation, and maintenance. The results of this study indicate that a web-based information system can significantly enhance transparency, efficiency, and accessibility of village information. However, challenges remain, particularly the lack of understanding and technological literacy among villagers and local government officials. To address this, continuous training and support are essential to ensure optimal system utilization. The successful implementation of this system requires collaboration from all stakeholders, including the government, academia, and the community, to achieve sustainable development in the village.